Cloning and characterization of two cDNAs coding for human von Willebrand factor. - J. Evan Sadler; B B Shelton-Inloes; J M Sorace; John M. Harlan; Koiti Titani; Earl W. Davie (1985)
A cDNA library was prepared in lambda gt11 bacteriophage from poly(A)+ RNA isolated from primary cultures of endothelial cells from human umbilical vein. Approximately 2.5 million independent recombinants were screened and 2 of those were found to synthesize a fusion protein with beta-galactosidase that reacted with rabbit antibody against human von Willebrand factor. Comparison of the amino acid sequence translated from the cDNA insert of the two clones with the amino acid sequence determined by Edman degradation of the protein established that both phage isolates code for von Willebrand factor. The first clone (lambda HvWF1) contained an insert of 404 nucleotides that corresponded to amino acid residues 1-110 in the mature protein circulating in blood, in addition to a portion (24 amino acids) of a prepro leader sequence. The second cDNA clone (lambda HvWF3) contained an insert of 4.9 kilobases that coded for the carboxyl-terminal 1525 amino acids of von Willebrand factor, a stop codon of TGA, 134 nucleotides of 3' noncoding sequence, and a poly(A) tail of 150 nucleotides. The two clones together code for greater than 80% of the molecule circulating in blood. The same carboxyl-terminal lysine residue was identified in the mature protein as well as in the cDNA, indicating that all of the proteolytic processing that occurs during the biosynthesis and assembly of von Willebrand factor is associated with the amino-terminal portion of the precursor protein. The amino acid sequence of von Willebrand factor indicates the presence of two different internal gene duplications and one triplication. These repetitive amino acid sequences account for about one-half of the amino acids present in the mature protein. The tetrapeptide sequence of Arg-Gly-Asp-Ser, which mediates the cell attachment and platelet binding activity of fibronectin, was also identified in the carboxyl-terminal portion of von Willebrand factor.